The effects of microstructure on wave velocity and wavefront in granular assemblies with binary-sized particles. (1st March 2019) - Wang, Jiao; Chu, Xihua; Zhang, Junbo; Liu, Hui
Abstract: The nonlinear behavior of highly ordered granular materials is due to their inability to transfer tensile loads and the Hertzian contact between particles. We investigated the propagation of stress waves excited by impulsive loadings in granular assemblies composed of an uncompressed, centered square array of spherical particles the radii of which are gradually increased. Systematic variations in the radius ratio of the surrounding and intruder particles lead to large variations in the characteristics of the wave velocity and propagating stress wavefronts traveling through the system. By assuming the dissipating rate of the contact interface, the pulse energy dissipation is obtained, which provides a solution to the calculation of the frictional energy consumption. The relationship between the microstructure and the wavefront shape is of concern. Finally, equations of the wavefront in hexagonal assemblies were analytically given which substantiated reasonable prediction of the wave propagation process through the assemblies.